2011
DOI: 10.1074/jbc.m111.253344
|View full text |Cite
|
Sign up to set email alerts
|

Taurine Biosynthesis by Neurons and Astrocytes

Abstract: The physiological roles of taurine, a product of cysteine degradation and one of the most abundant amino acids in the body, remain elusive. Taurine deficiency leads to heart dysfunction, brain development abnormalities, retinal degradation, and other pathologies. The taurine synthetic pathway is proposed to be incomplete in astrocytes and neurons, and metabolic cooperation between these cell types is reportedly needed to complete the pathway. In this study, we analyzed taurine synthesis capability as reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(81 citation statements)
references
References 40 publications
3
73
0
Order By: Relevance
“…It has been indicated that both compounds, besides various still debated biological functions 51, 52, 53, 54, 55, play a determining contribution in controlling cerebral osmolarity 52, 55, 56. Even though some studies showed a decrease in Tau after TBI 57, 58, 59, our results are in line with those reported by others 60, 61 and are logically connected to dysfunctional NAA homeostasis following sTBI and to a precise role of osmolite regulator performed by cerebral Tau.…”
Section: Discussionmentioning
confidence: 99%
“…It has been indicated that both compounds, besides various still debated biological functions 51, 52, 53, 54, 55, play a determining contribution in controlling cerebral osmolarity 52, 55, 56. Even though some studies showed a decrease in Tau after TBI 57, 58, 59, our results are in line with those reported by others 60, 61 and are logically connected to dysfunctional NAA homeostasis following sTBI and to a precise role of osmolite regulator performed by cerebral Tau.…”
Section: Discussionmentioning
confidence: 99%
“…8B). Hypotaurine, an amino acid derivative that may function as a neurotransmitter or an antioxidant in addition to its role in osmolyte balance (37,38), was the most dramatically upregulated metabolite in the Mpc1 KI/KI brain at more than 15 times the concentration in the WT brain (Fig. 8B).…”
Section: Mpc Deficiency Promotes Metabolic Plasticity In Uteromentioning
confidence: 99%
“…Moreover, taurine deficiency is associated with various pathologies including heart dysfunction [31], abnormalities of brain development [32], and cardiomyopathy [33]. In the astrocytes and the neurons, taurine is the principal osmolyte which during hypotonic or hypertonic conditions it goes out from or accumulates inside the cell, respectively [12]. Melani and colleagues used the brain microdialysis technique and demonstrated that after middle cerebral artery occlusion in the rat taurine was increased in the dialysate samples [34].…”
Section: Discussionmentioning
confidence: 99%
“…Taurine is also one of the most abundant free amino acids in the heart, brain, liver, retina and skeletal muscles [12]. Taurine is also the second most abundant amino acid in the brain after glutamate [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation